The future of mandatory takeover offer: a case study on Malaysia - Ambaras Khan, Mushera Bibi; Alias, Suzana Norlihan; Muhtah, Hnadi (Springer Nature Singapore Pte. Ltd., 2017)
Takeover and acquisition have been part of the business world for centuries. Due to rapidly growing economic and environment challenges, companies have to face making decisions concerning these engagements. It requires careful and wise decision-making since the job of a company's management is to get the most out of its shareholder value. The Malaysia law imposes a requirement on the bidder who obtains control over the target company to make a mandatory offer simply to protect the shareholders of the latter by giving them the opportunity ti participate in benefits accruing from mandatory take over and be treated equally in relation to it. The mandatory offer, deeply rooted in the UK law, finds its way into Malaysia through law transplantation. A combination of library and empirical research carried out by the author is employed as the methodology in this chapter. The authors argue that the implications for the implementations of a mandatory offer in particular in Malaysia and other ASEAN Commonwealth countries do not bring the same result as expected in UK due to the concentrated shareholding structure nature in ASEAN companies as opposed to the dispersed shareholding structure in UK companies. This chapter highlighted the pros and cons of a mandatory offer and its future in takeover laws.